Sams teach yourself Mac OS X Panther all in one - Ness, Robyn (Sams, 2004)
Sams Teach Yourself Mac OS X Panther All in One is designed to teach, in one big book, the new Mac user how to easily work with his hardware, his operating system, and all the applications he is likely to want to use to work with digital media. The book does not assume the reader wants to learn how to use just one product, but covers multiple products and technologies together in a logical fashion. Setting up and configuring Mac hardware. Understanding the Mac OS X interface. Burning CDs and DVDs with iDVD. Playing and organizing MP3s and digital music with iTunes. Digital photography with iPhoto. Editing digital video with iMovie.
Print version record
Keywords: Mac OS; Operating systems (Computers); Macintosh (Computer) -- Programming; Multimedia systems -- Programming; Systèmes d'exploitation (Ordinateurs); Macintosh (Ordinateur); Programmation; Multimédia; Programmation; operating systems; COMPUTERS; Operating Systems; Macintosh; Macintosh (Computer); Programming; Multimedia systems; Programming